Identification and Biological Activity of the Active Metabolite of Clopidogrel - Savi, P.; Pereillo, J. M.; Uzabiaga, M. F.; Combalbert, J.; Picard, C.; Maffrand, J. P.; Pascal, M.; Herbert, J. M. (Thrombosis and Haemostasis, 2000)
Like ticlopidine, the ADP receptor antagonist clopidogrel is inactive in vitro and must be administered i.v. or orally to exhibit antiaggregatory and antithrombotic activities. We have previously shown that hepatic metabolism is necessary for activity. This study demonstrates that an active metabolite can be generated from human liver microsomes incubated with clopidogrel. Using several analytical methodologies (LC/MS, NMR, chiral supercritical fluid chromatography), we have identified its structure. In vitro, this highly unstable compound, different from that formed from ticlopidine, exhibited all the biological activities of clopidogrel observed ex vivo: Irreversible inhibition of the binding of 33P-2MeS-ADP to washed human platelets (IC50 = 0.53 µM), selective inhibition of ADP-induced platelet aggregation (IC50 = 1.8 µM) and ADP-induced adenylyl cyclase down-regulation. The irreversible modification of the ADP-receptor site which is responsible for the biological activity could be explained by the formation of a disulfide bridge between the reactive thiol group of the active metabolite and a cysteine residue of the platelet ADP receptor.Abbreviations: ADP: adenosine 5’diphosphate; 2-MeS-ADP: 2-methylthioadenosine-5’-diphosphate; Bmax: maximum binding capacity; IC50: concentration which inhibits 50% of the activity; Kd: dissociation constant; LC/MS: Liquid chromatography coupled to mass spectrometry; NMR: Nuclear magnetic resonance
Keywords: Clopidogrel; ADP; aggregation; platelets; metabolite